α-Conotoxins - Arias, Hugo Rubén (2000)
α-Conotoxins (α-CgTxs) are a family of Cys-enriched peptides found in several marine snails from the genus Conus. These small peptides behave pharmacologically as competitive antagonists of the nicotinic acetylcholine receptor (AChR). The data indicate that (1) α-CgTxs are able to discriminate between muscle- and neuronal-type AChRs and even among distinct AChR subtypes; (2) the binding sites for α-CgTxs are located, like other cholinergic ligands, at the interface of α and non-α subunits (γ, δ, and ε for the muscle-type AChR, and β for several neuronal-type AChRs); (3) some α-CgTxs differentiate the high- from the low-affinity binding site found on either α/non-α subunit interface; and that (4) specific residues in the cholinergic binding site are energetically coupled with their corresponding pairs in the toxin stabilizing the α-CgTx-AChR complex. The α-CgTxs have proven to be excellent probes for studying the structure and function of the AChR family.